A lagarta de Cerconota achatina (Zeller) (Lepidoptera, Oecophoridae, Stenomatinae): biologia e ocorrência em plantas hospedeiras do gênero Byrsonima Rich (Malpighiaceae) - Andrade, I (1995)
Caterpillars of Cerconota achatina (Zeller, 1855) feed on lhe leaves of Byrsonima Rich in cerrado (savanna) of Brasília (Distrito Federal). They build shelters by tying leaves together with silk and frass. Within the leaf shelters the caterpillars form a tube of silk in which they feed. develop and pupate. In the laboratory the pupal stage is 14,4 days (sd=8,6: n=46). It was not possible to determine the age or numbers of instars of caterpillars in the wild. Of 93 caterpillars collected. 60% were feeding on B. cocclohifolia (Spr.) Kunth, 25% on B. crassa Nied. and 15% on B. verbascifolia [Rich. ex] Adr. & Juss. These numbers suggest a preference for B. coccolobifolia. Caterpillars of all size were found in every month of the year which suggest ovelapping generations and multivoltinism. They did not show a preference for new foliage and 75% of them were found on host-plants on wich less than 25% of leaves were young.